Personality, Attitude and Behavioural Components of Financial Literacy: A Comparative Analysis - enemeth, Erzsabet; Zsoter, Boglarka (Journal of Economics and Behavioral Studies, 2017)
Since the financial crisis in 2008 the investigation of financial literacyâ€“especially its components (personality, attitudes, behaviour etc.) - is in the limelight. Modern economics have recognized that in order to effectively forecast financial and economic processes it is primordial to understand the attitudes of the members of society toward finances, as well as the characteristics of various social group sharing the same views and behaviours. In 2015 two relevant pieces of research were conducted in this topic in Hungary. One focuses on the financial personality types, while the other investigates Hungariansâ€™ financial culture in general based on the research methodology of the OECD. Based on these two databases our comparative study highlights the main characteristics of financial personality types. The three clusters based on the OECD research cover the nine personality types from the results of the other Hungarian research. Our findings show that the cluster of â€œanxious unsatisfiedâ€ encapsulates the â€œeconomizers with little moneyâ€, the â€œprice sensitiveâ€ and the â€œcollectorâ€ personality types. Furthermore, the â€œsatisfied consciousâ€ covers the â€œorder creates valueâ€, the â€œdiligentâ€ and the â€œplannerâ€ personality types. Finally, the â€œmoderately anxious unconsideredâ€ involves the â€œups and downsâ€, the â€œmoney-devouringâ€ and the â€œcannot control financesâ€ personality types. The clusters identified during the research show idiosyncratic financial and psychological vulnerability and/or protection.